ANALISIS SANITASI KAPAL DENGAN TANDA KEBERADAAN KECOA PADA KAPAL PENUMPANG DI KANTOR KESEHATAN PELABUHAN KELAS II SAMARINDA - Ratna Yuliawati; Wisnu Adi Prasetyo; Vita Pramaningsih; Rusdi Rusdi (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
Ship sanitation is one of the efforts aimed at environmental health risk factors on board. The results obtained from the Port Health Office (KKP) Class II Samarinda, there are several types of ships that are routinely carried out sanitary inspections of ships, one of which is a passenger ship. Therefore, researchers want to examine the Sanitary Relationship of Ships With Signs of The Presence of Cockroaches On Passenger Ships Leaning in The Port of Class II Samarinda. The design of this study is an observational analytical method with cross sectional study design. The instruments in this study used the ship's sanitation inspection form and the cockroach inspection form on the passenger ship. The data is processed using Fisher Exact Test. Based on the results of the study, where the 5 vessels that were examined have met the sanitary requirements (100%) in accordance with The Minister of Health Regulation No. 40 of 2015 concerning Certificate of Ship Sanitation. The results of the study found signs of the presence of cockroaches on the ship as many as 4 units of ships (80%). The results of statistical tests processed by Fisher Exact Test obtained the following results, p-value count = 0.20 > from p-value α = 0.05 so that the conclusion H0 received, which means